Occurrence and antimicrobial susceptibility of thermophilic Campylobacter species isolated from healthy children attending municipal care centers in Southern Ecuador - Toledo, Zorayda (2017)
The prevalence and antimicrobial susceptibility of Campylobacter jejuni and C. coli strains in healthy, well-nourished children of middle socioeconomic level from Southern Ecuador were determined. Among the 127 children studied, 17 (13.4%) harbored Campylobacter sp. corresponding to C. jejuni (7.1%) and C. coli (6.3%) with a higher concentration of C. jejuni among boys (8.6%) and C. coli (8.8%) among girls. C. jejuni showed high resistance to nalidixic acid and ciprofloxacin (77.8%), but susceptibility to all other antimicrobials tested. C. coli strains showed resistance to more antibiotics than C. jejuni strains including resistance to nalidixic acid (75%), ciprofloxacin (75%), erythromycin (12.5%) and ampicillin (28.6), but susceptible to gentamicin and amoxicillin/clavulanic acid.